Analysis of The Influence of Profit Value and Restaurant Ambience on Return Visit Intention Mediated by Customer Satisfaction (A Case Study of Restaurant Consumers in Surakarta) - Salsabila, Zahrotus (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2023)
This study aims to analyze the effect of perceived value and restaurant atmosphere on customer satisfaction which will then influence customer intentions to revisit. Researchers used 151 people as a sample with the criteria of having eaten at a restaurant at least once. According to the criteria of the respondents who have been determined, the sampling method using purposive sampling. Data were analyzed using SEM-PLS and processed using Smart PLS 3. The findings verified the value of the benefits perceived by customers and the atmosphere of the restaurant had a significant positive effect on customer satisfaction. Customer satisfaction was confirmed as a significant positive effect on revisit intention.